Peralihan Sucker Rod Pump (SRP) ke Electrical Submersible Pump (ESP) pasca Workover Sebagai Upaya Optimalisasi Produksi Sumur “E-030” - Evi Maulia Nilawati; Deny Fatrianto Edyzoh Eko Widodo; M. Nur Mukmin; Fatma; Aprilliano Alfa Kumarsela; Cindy Pebriana; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
Optimizing artificial lift systems according to well conditions is essential to achieve the desired production rate. Continuous production often leads to declining flow rates and reservoir pressure, causing incomplete fluid recovery. Water injection helps maintain pressure, while workover operations enhance production rates. This study optimizes well "E-030" by redesigning the artificial lift system from a Sucker Rod Pump (SRP) to an Electrical Submersible Pump (ESP) post-workover. The goal is to evaluate pre-workover production, justify the workover, and assess the redesigned lift system's efficiency. Initially, well "E-030" used an SRP. Due to a water flooding project, a workover was conducted, adding production layers to boost capacity. The best artificial lift post-workover was determined using an Inflow Performance Relationship (IPR) curve, applying Wiggin's method to analyze well conditions. The post-workover IPR analysis showed a maximum flow rate of 1104 bfpd and an optimal rate (Qopt) of 883 bfpd, a significant increase from 145 bfpd pre-workover. This led to replacing the SRP with an ESP to accommodate higher production. The redesigned ESP system includes a REDA D725N pump, a REDA 456 series motor, and AWG#4 cable, improving production efficiency.